Solution structure of Phrixotoxin 1, a specific peptide inhibitor of Kv4 potassium channels from the venom of the theraphosid spider Phrixotrichus auratus - Chagot, Benjamin (Cold Spring Harbor Laboratory Press, 2004)
Animal toxins block voltage-dependent potassium channels (Kv) either by occluding the conduction pore (pore blockers) or by modifying the channel gating properties (gating modifiers). Gating modifiers of Kv channels bind to four equivalent extracellular sites near the S3 and S4 segments, close to the voltage sensor. Phrixotoxins are gating modifiers that bind preferentially to the closed state of the channel and fold into the Inhibitory Cystine Knot structural motif. We have solved the solution structure of Phrixotoxin 1, a gating modifier of Kv4 potassium channels. Analysis of the molecular surface and the electrostatic anisotropy of Phrixotoxin 1 and of other toxins acting on voltage-dependent potassium channels allowed us to propose a toxin interacting surface that encompasses both the surface from which the dipole moment emerges and a neighboring hydrophobic surface rich in aromatic residues.